Aswaja NU dan Toleransi Umat Beragama - Fathurrohman, Fathurrohman (Jurnal Review Politik, 2012)
Democracy like a double-edged sword, having a positive and negative impacts as well. The positive things of democracy are respect and giving space for minorities to gain equal opportunities in all areas, and creating justice. However, the opening of opportunities to the minorities create friction escalation of religious conflict, ethnicity and culture. This paper will describe the concept of Aswaja of Nahdlatul Ulama and their impact on socio-religious life. The findings of this study states that the concept of Aswaja like tawassuth sifat: i'tidâl, tasâmuh, tawazun, ta'âruf, ta'âwan, and tawâshaw are directly proportional to the tolerance that describes the concept of mutual respect and mutual cooperate on among community groups.